Development of Community Economic Empowerment Model through Pioneering Tourism Village Training in Indonesia - Purbaningrum, Catarina Wahyu Dyah; ., Sukirno; ., Saliman; Raharjo, Semiono (Journal of Ecohumanism, 2024)
This study aims to produce a model of community economic empowerment through training in pioneering tourist villages that is feasible, practical, and effective. The research method uses Research and Development (R&D) adaptation of the Borg and Gall model, involving the subjects of managers and the community in Gunungkidul Regency, Indonesia. The research data were obtained using (1) qualitative methods, with data triangulation, observation, interviews, and documentation; (2) quantitative, with validation of models and instruments, practicality and effectiveness of the model. The results of the study: (1) The product of the community economic empowerment model through training in pioneering tourist villages meets the criteria for feasibility as indicated by the results of expert assessments; (2) The community economic empowerment model through training was implemented well and met the criteria for practicality based on observer assessments; and (3) There was an increase in the understanding of training participants effectively. The results of this study indicate that the community economic empowerment model through training in pioneering tourist villages has proven to be feasible, practical, and effective for community economic empowerment and can be used as a recommendation for local and central governments in developing tourist villages.